2007
DOI: 10.1002/bip.20764
|View full text |Cite
|
Sign up to set email alerts
|

Merozoite surface protein 2 of Plasmodium falciparum: Expression, structure, dynamics, and fibril formation of the conserved N‐terminal domain

Abstract: Merozoite surface protein 2 (MSP2) is a GPI-anchored protein on the surface of the merozoite stage of the malaria parasite Plasmodium falciparum. It is largely disordered in solution, but has a propensity to form amyloid-like fibrils under physiological conditions. The N-terminal conserved region (MSP2(1-25)) is part of the protease-resistant core of these fibrils. To investigate the structure and dynamics of this region, its ability to form fibrils, and the role of individual residues in these properties, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
53
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 41 publications
(62 citation statements)
references
References 47 publications
9
53
0
Order By: Relevance
“…Another vaccine candidate merozoite surface protein MSP2, which is a GPI-anchored ϳ30-kDa highly abundant protein, was also shown to form amyloid-like fibrils under physiological conditions as observed for MSP3 in this study (50,51). Structurally, MSP2 has two conserved domains at the N and C termini but is highly polymorphic in the central region.…”
Section: Discussionsupporting
confidence: 63%
“…Another vaccine candidate merozoite surface protein MSP2, which is a GPI-anchored ϳ30-kDa highly abundant protein, was also shown to form amyloid-like fibrils under physiological conditions as observed for MSP3 in this study (50,51). Structurally, MSP2 has two conserved domains at the N and C termini but is highly polymorphic in the central region.…”
Section: Discussionsupporting
confidence: 63%
“…Importantly, both the 3D7 and FC27 allelic forms of MSP2 showed the same phenotype of being carried into RBCs followed by rapid degradation. The 3D7 and FC27 alleles of MSP2 share N-and C-terminal regions but vary significantly in the central strain-specific region of the protein (46,(76)(77)(78). The observation that both MSP2 variants show the same localization and very precise timing of degradation postinvasion suggests that the functions of the 3D7 and FC27 forms of MSP2 are the same, despite any structural differences.…”
Section: Discussionmentioning
confidence: 99%
“…One of these MAbs, 6D8, is the only MAb identified that reacts with the short conserved N-terminal region of MSP2, which was previously established to be responsible for the formation of amyloid-like fibrils by MSP2 (1,30). The failure to detect this epitope on the merozoite surface was not due to removal of this region of MSP2 by proteolytic processing because polyclonal rabbit antibodies to the N-terminal conserved region of the antigen did react with the merozoite surface by IFA (data not shown).…”
Section: Discussionmentioning
confidence: 99%